2024 Florida Blueberry Integrated Pest Management Guide: HS380/HS1156, rev. 8/2024 - Harmon, Philip; Liburd, Oscar; Dittmar, Peter; Williamson, Jeffrey; Phillips, Doug (EDIS, 2024)
This publication is intended to be a resource for Florida blueberry growers to use in scouting for disease and insect/mite pest damage; managing disease, insect/mite pests, and weeds; and application of certain plant growth regulators.